Data-driven marketing : the 15 metrics everyone in marketing should know - Jeffery, Mark, 1965- (Hoboken, N.J. : John Wiley, 2010)
"Every marketing department is under pressure to deliver, but some will thrive and some won't. Data-Driven Marketing provides top-to-bottom coverage of what works, what doesn't, and what makes the difference in this important but misunderstood area."--Jacket.
Data-Driven Marketing: The 15 Metrics Everyone in Marketing Should Know; CONTENTS; DOWNLOADABLE ROMI RESOURCES; ACKNOWLEDGMENTS; INTRODUCTION; Part I: Essentials; Chapter 1: The Marketing Divide; Chapter 2: Where Do You Start?; Chapter 3: The 10 Classical Marketing Metrics; Part II: 15 Metrics to Radically Improve Marketing Performance; Chapter 4: The Five Essential Nonfinancial Metrics; Chapter 5: Show Me the ROI!; Chapter 6: All Customers Are Not Equal; Chapter 7: From Clicks to Value with Internet Marketing Metrics; Part III: The Next Level; Chapter 8: Agile Marketing.
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Marketing research; Marketing -- Mathematical models; Marketing -- Case studies; Marketing -- Recherche; Marketing; Marketing; BUSINESS & ECONOMICS -- Marketing -- Research; Marketing; Marketing -- Mathematical models; Marketing research; Effizienzmessung; Leistungskennzahl; Marketing; Marketingaudit; marketing -- 2; marketing -- 2; marketing -- 2; Case studies